Dendroclimatological approach in plantation management of teak (Tectona grandis) - SINHA, SATISH KUMAR; BEHERA, LAXMIKANTA; MEHTA, ABHISHEK; SHRIVASTAVA, PRASHANT KUMAR (The Indian Journal of Agricultural Sciences, 2019)
Teak (Tectona grandis Linn f.) is a commercial timber species which has been widely studied for dendroclimatology. The objective of the investigation was to utilize dendroclimatological approach in plantation management for teak growers. To monitor the effect of climatic factors, viz. rainfall and temperature on the radial growth of teak, 37 core samples from 29 teak trees were collected at three different sites, viz. Ahwa (Dang), Valsad during December, 2012 and Navsari of South Gujarat during January, 2015. It was observed that pre-monsoon showers and high temperature during March and monsoon rainfall during June–July and September of the current year have positive influence on the radial growth of teak at Ahwa site. However, there was positive influence of previous and current year’s September–November rainfall on the radial teak growth at Navsari site. At Valsad site, previous year’s August rainfall and current year’s June rainfall had significant negative correlation with radial growth of teak. Temperature of previous year’s October–December and current year’s July and September–November months also showed significant negative relationship with radial growth. It was observed that rainfall during March month was positively correlated with radial growth of teak at three sites however, it was significant only at Ahwa site. Hence, it is concluded from the study that for boosting up the radial growth of teak, the growers should give water in the form of light irrigation during March and normal irrigation during active growing period from June–September especially when there is a moisture stress due to deficient rainfall.